Interprocessus distances based on gender using panoramic radiographs - Eha Renwi Astuti; Otty Ratna Wahyuni; Dina Karimah Putri; Nastiti Faradilla Ramadhani; Ramadhan Hardani Putra; Azifah Shafa Izdihar; Khusnul Rahmawati (Ikatan Radiologi Kedokteran Gigi Indonesia, 2022)
Objectives: This research is aimed to find out the differences of interprocessus distances between males and females using panoramic radiographs. Materials and Methods: This research is using observational analytic with cross sectional study design. Secondary data was taken from 96 panoramic radiographs consisting of 48 males and 48 females, from RSKGM-P Universitas Airlangga. Measurements were carried out using ImageJ Software by 3 observers. The measurement results were then analyzed by independent t-test and the inter-measuring reliability was tested using the Intraclass Correlation Coefficient (ICC) on IBM SPSS software. Results: The result showed that the significance value (2-tailed) of interprocessus distances measurement on males and females was <0.05 in both regions. Reliability test of inter-observer using ICC obtained the overall measurement results was more than 0.75 which means excellent reliability. Conclusion: There was a significant difference between the interprocessus distances on males and females as measured by panoramic radiographs.